Phylogenetic study of metallo-β-lactamase producing multidrug resistant Pseudomonas aeruginosa isolates from burn patients. Issue 8 (December 2015) - Jena, Jayanti; Debata, Nagen Kumar; Sahoo, Rajesh Kumar; Subudhi, Enketeswara
Highlights: High %MBL producers were observed by IPM-EDTA disk diffusion test. High genetic diversity was observed among 11 MBL producing strains. CL, TGC and IC were highly active against MBL producing P. aeruginosa in vitro . Abstract: The present study was carried out to understand the clonal relationship using enterobacteriaceae repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) among metallo-β-lactamase (MBL) producing multidrug resistant Pseudomonas aeruginosa isolates from burn victims and their susceptibility to commonly used anti-pseudomonal agents. In the present study 94 non-duplicate P. aeruginosa strains from the wound samples of burn patients were included. Identification of the isolates was done by biochemical methods and antibiotic sensitivity was done by disc diffusion method following CLSI (Clinical Laboratory Standard Institute) guidelines. By using imipenem (IPM)-EDTA disk diffusion/double disc synergy method carbapenem resistant organisms were tested for MBL. To define the clonal relationship ERIC-PCR was used. Of the 94 isolates, 18 (19.14%) were found resistant to IPM and MBL production was shown 11 (11.70%) by the IPM-EDTA disc diffusion method. From dendrogram of the ERIC-PCR profile four major clusters were obtained (A, B, C and D). Cluster B contained the majority of the isolates (6 strains 1, 4, 8, 9, 10 and 11). This study using ERIC-PCR of randomly collected isolates exhibits high genetic diversity which rules out cross contamination frequency.